Personality traits and investment decision - Shahu, Dil Krishna (Journal of Nepalese Management Academia, 2023)
This study aims at examining the relationship between personality traits and investment decision. The study used empirical research methodology using primary sources of information collected using structure questionnaire. Multiple linear regression was used to analyze the linear relationship between the personality dimensions and investment decision-making. The personality traits considered for the study are extraversion, agreeableness, conscientiousness, neuroticism, and openness. The study provided empirical evidence that the personality trait of conscientiousness and extroversion have a significant positive influence on the investment decision making process of retail investors. Similar, neuroticism has positive effect on investment decision of investor and statistically significant at 10 percent level of significance. The results of the study could help investors better understand their investment decision-making in terms of the influence of their personality. Financial advisors could also benefit from this study as it would allow them to correlate their clients’ personalities and decision-making tools and suggest the most appropriate investment strategies.